Fecal Microbiota Transplantation-Mediated Rebalancing of the Gut-Brain Axis Alleviates Cisplatin-Induced Neuropathic Pain - Rani M.; Akhilesh N.; Chouhan D.; Uniyal A.; Tiwari V. (My University, 2025)
Chemotherapy-induced neuropathic pain (CINP) presents a significant challenge in cancer treatment, necessitating novel therapeutic approaches. The intricate relationship between CINP and the gut-brain axis indicates a crucial role for the gut microbiota in pain modulation during cancer therapy. In this study, we investigated the effect of gut microbiota and their modulation on CINP in rats. Cisplatin administration (20 mg/kg, ip) disrupted the integrity of the blood-spinal cord barrier, as evidenced by reduced expression of tight junction proteins occludin and claudin-5 and increased leakage of pro-inflammatory cytokines into the spinal cord. Fecal microbiota transplantation (FMT, 0.5 mL of P.O.) from healthy rats over 21 days restored barrier integrity, as confirmed by Evan’s blue assay. FMT intervention halted the progression of cisplatin-induced pain, demonstrated through a battery of pain assays assessing mechanical, thermal, and cold allodynia alongside hyperalgesia measurements. Additionally, FMT treatment reduced oxidative stress and modulated neuro-inflammatory markers, resulting in a rebalanced cytokine profile with decreased levels of neuro-inflammatory cytokines (IL-6 and TNFα) and increased expression of the anti-inflammatory cytokine IL-10. Gut microbiota-mediated IL-1β/NF-κB signaling emerged as a critical factor in leukocyte recruitment and microglial activation, highlighting the gut-brain axis as a key regulatory nexus in managing cisplatin-induced neuropathic pain. These findings underscore the therapeutic potential of targeting gut microbiota modulation as a promising strategy for alleviating CINP and improving the well-being of cancer patients undergoing chemotherapy. © 2024 American Chemical Society.